Quality Control of b100 Biodiesel Obtained from soy Biodiesel Processing - Technical Note - Berwanger, Cinthia da Costa; Vasconcellos, Noeli Júlia Schüssler de; Peixoto, Sandra Cadore; Swarowsky, Alexandre; Salazar, Rodrigo Fernando dos Santos (Ciência e Natura, 2015)
The growing demand for energy and the depletion of non-renewable sources has generated a search for different energy sources, especially those that are renewable. In this context biodiesel presents itself as one of the most interesting energy source because of its renewable character and achievement of a number of society sectors with its diversified production chain in different locations. In this sense, the objective of this study was to evaluate the physicochemical characteristics of the biodiesel B100 produced industrially in Rio Grande do Sul during 2012 year. We determined the combined alkalinity, free glycerin content, total glycerin content, acid index and moisture content which ranged around 0.0002 meq/ g, 0.024% w / w, 0.21% w / w to 33 mg KOH / g and 343.7 mg / kg, respectively. These values were in accordance with current legislation. Thus it is concluded that the chemical process of trans-esterification was kept under control during the production period of the resulting biodiesel in a reliable energy source